2009
DOI: 10.1021/jm900495f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fluorinated Brassinosteroids Based on Alkene Cross-Metathesis and Preliminary Biological Assessment

Abstract: Three types of brassinosteroid analogues with perfluoroalkylated side chains were synthesized by using alkene cross-metathesis of a brassinosteroid derivative bearing a terminal alkene moiety with different (perfluoroalkyl)propenes. The presence of the double bonds in the cross-metathesis products allowed a facile one-step double dihydroxylation to provide intermediates that after Baeyer-Villiger oxidation afforded the target compounds. Biological activity of the prepared analogues was tested in GABA(A) recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Only catalysis by Hoveyda–Grubbs 2 nd generation catalyst gave the desired product 3 in 14% yield. The suitability of Hoveyda–Grubbs 2 nd generation catalyst for cross-metathesis reactions was consistent with the previously observed results [5–8]. Further tuning of the reaction conditions showed that the best yields were obtained by carrying out the reaction in toluene at 120 °C for 16 h (Scheme 1).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Only catalysis by Hoveyda–Grubbs 2 nd generation catalyst gave the desired product 3 in 14% yield. The suitability of Hoveyda–Grubbs 2 nd generation catalyst for cross-metathesis reactions was consistent with the previously observed results [5–8]. Further tuning of the reaction conditions showed that the best yields were obtained by carrying out the reaction in toluene at 120 °C for 16 h (Scheme 1).…”
Section: Resultssupporting
confidence: 90%
“…Recently, we have shown that metathesis of various terminal alkenes with perfluoroalkylpropenes constitutes a simple and efficient approach for the synthesis of wide array of perfluoroalkylated compounds [4]. This methodology was then applied for the synthesis of perfluoroalkylated analogs of brassinosteroids [5], 17α-perfluoroalkylestradiols [6], perfluoroalkylcyclodextrins [7], and perfluoroalkylcarboranes [8]. Successful execution of these reactions prompted us to study also cross-metathesis of allylcarboranes with O -allylcyclodextrins as a route to carborane-cyclodextrin conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…4). A norcastasterone hepta-fluorinated derivative 18 was the only analogue of this type which exhibited a slight cytotoxicity (IC 50 = 35.3 lM against CEM cell line) [120]. A distinct cytotoxicity (IC 50 = 7-15.8 lM) against MGC 7901 (human gastric carcinoma), HeLa (human cervical carcinoma) and SMMC 7404 (human liver carcinoma) cells displayed cholestane lactones 19 and 20 [121].…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…In contrast to common alkenes, the metathesis of fluoroalkenes has attracted far less attention [ 23 ]. Fluorinated modifications have mostly concentrated on the side chain of the vinyl group [ 24 27 ] or applications of 2-fluoroalkenes [ 28 30 ]. As an exception, the reaction of the Grubbs 2 nd generation catalyst with 1,1-difluoroethene gave an isolable difluoromethylene-containing ruthenium complex with very poor catalytic activity [ 31 ] and the analogous reaction of 1-fluoroalkene formed a fluoromethylene-containing complex with low catalytic activity [ 32 33 ].…”
Section: Introductionmentioning
confidence: 99%